TDABC IMPLEMENTATION IN MANUFACTURING FIRMS AND SMES: A CONTINGENCY-BASED SYSTEMATIC LITERATURE REVIEW - Silvi Yanti Yanti; Andry Arifian Rachman (Universitas Tulungagung, 2026)
This study examines the implementation and outcomes of Time-Driven Activity-Based Costing (TDABC) in manufacturing firms and small and medium-sized enterprises (SMEs) through a Systematic Literature Review (SLR). The study aims to analyze TDABC implementation practices, evaluate its effectiveness compared with alternative costing methods, identify implementation challenges and success factors, and explore its contribution to operational efficiency and organizational sustainability. Following the PRISMA guidelines, the review synthesized evidence from 97 peer-reviewed journal articles published between 2010 and 2025. The findings indicate that TDABC improves cost allocation accuracy by utilizing capacity cost rates and time equations, providing more reliable information for managerial decision-making. Compared with traditional costing systems and conventional Activity-Based Costing (ABC), TDABC offers greater flexibility and supports more effective resource allocation. The review further reveals that operational and production efficiency is the dominant outcome of TDABC implementation, reflected in improved resource utilization, waste reduction, and process optimization. In addition, TDABC implementation is influenced by contextual factors such as process complexity, digitalization, data quality, ERP integration, and managerial support. These findings support a contingency perspective of TDABC implementation and highlight its role as a strategic management tool that contributes to organizational performance and sustainability.